Employee Performance in Multinational Companies: The Role of Culture and Motivation - Rahmawati, Ika Rahmawati; Nurhidayah, Nurhidayah; Basalamah, Muhammad Ridwan (Amkop Management Accounting Review (AMAR), 2025)
Organisational culture and work motivation are crucial factors that influence employee performance in multinational companies, but the complex relationship between these variables is still not comprehensively explained. This study aims to analyse the influence of organisational culture and work motivation on employee performance using a Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) approach. Data were collected from 250 employees of multinational companies in the ASEAN region using proportional stratified random sampling technique. The results of the analysis show that organisational culture and work motivation have a positive and significant effect on employee performance, with work motivation also acting as a partial mediator in the relationship between organisational culture and performance. The findings confirm the importance of integrating a strong organisational culture and effective motivational strategies to improve employee performance across cultures. The practical implications of this study provide guidance for human resource management in multinational companies to develop an inclusive work culture and motivational programmes that are adaptive to cultural diversity. This research also opens up opportunities for further studies with longitudinal designs and mixed methods approaches to deepen the understanding of the dynamics of the variable relationships.